Death wears a mask [large type] : a mystery - Weaver, Ashley (Weaver, Ashley. Amory Ames mystery., 2016)
"Amory Ames is looking forward to a tranquil period of reconnecting with reformed playboy husband Milo after an unexpected reconciliation following the murderous events at the Brightwell Hotel. Amory hopes a quiet stay at their London flat will help mend their dysfunctional relationship. However, she soon finds herself drawn into another investigation when Serena Barrington asks her to look into the disappearance of valuable jewelry snatched at a dinner party. Unable to say no to an old family friend, Amory agrees to help lay a trap to catch the culprit at a lavish masked ball hosted by the notorious Viscount Dunmore. But when one of the illustrious party guests is murdered, Amory is pulled back into the world of detection, enlisted by old ally Detective Inspector Jones. As she works through the suspect list, she struggles to fend off the advances of the very persistent viscount even as rumors swirl about Milo and a French film star. Once again, Amory and Milo must work together to solve a mystery where nothing is as it seems, set in the heart of 1930s society London. Death Wears a Mask is the second novel in Ashley Weaver's witty and stylish Amory and Milo Ames mystery series"--